Entropy processing of diagnostic parameters - Kondratiev Aleksandr Evgenievich (Trends in Computer Science and Information Technology - Peertechz Publications, 2023)
Modern means of energy transportation are subject to the highest conditions in terms of operational reliability. This is achieved not only by the use of advanced technologies but also by constant monitoring of the technical condition. One method is vibration control, which involves processing the desired signal in various ways, one of which is the entropy method. The purpose of the work is to increase the reliability of the assessment of the technical condition of pipelines.